Improving Student's Writing through Portfolio Assessment - Sri Widayati (Universitas Negeri Malang, 2016)
This study aims at improving student's writing in terms of content, organization, and language use through the implementation of portfolio assessment. This classroom action research is descriptive qualitative in nature and was conducted in only one cycle consisting of four stages of activities. Twenty-six students taking Writing II course were taken as the subject and the main data was the paragraphs the students wrote throughout the semester. The instruments of data collection include rubric, self-reflection sheet, field notes, and questionnaire. The results show that portfolio assessment has increased the quality of students' writing as indicated by the difference between the scores they achieved for the pre-test and post-test, and by the rise of scores they achieved for the three paragraphs the students selected to be included in the portfolio